2018
DOI: 10.1094/mpmi-06-17-0136-r
|View full text |Cite
|
Sign up to set email alerts
|

A Verticillium dahliae Extracellular Cutinase Modulates Plant Immune Responses

Abstract: Cutinases have been implicated as important enzymes during the process of fungal infection of aerial plant organs. The function of cutinases in the disease cycle of fungal pathogens that invade plants through the roots has been less studied. Here, functional analysis of 13 cutinase (carbohydrate esterase family 5 domain-containing) genes (VdCUTs) in the highly virulent vascular wilt pathogen Verticillium dahliae Vd991 was performed. Significant sequence divergence in cutinase family members was observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 95 publications
4
73
0
Order By: Relevance
“…In our previous study, we found that V. dahliae can deliver the effector VdCBM1, a protein that also contains four cysteine residues and is a secreted SCP that suppresses PTI (Gui et al , ). VdCBM1 can also suppress the immunity triggered by damage‐associated molecular patterns (DAMPs), including the products from VdCUT11 (Gui et al , ). In this study, we rediscovered that the immunity triggered by VdSCPs in a BAK1/SOBIR1‐dependent manner is also suppressed by VdCBM1 (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we found that V. dahliae can deliver the effector VdCBM1, a protein that also contains four cysteine residues and is a secreted SCP that suppresses PTI (Gui et al , ). VdCBM1 can also suppress the immunity triggered by damage‐associated molecular patterns (DAMPs), including the products from VdCUT11 (Gui et al , ). In this study, we rediscovered that the immunity triggered by VdSCPs in a BAK1/SOBIR1‐dependent manner is also suppressed by VdCBM1 (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…In Phytophthora sojae , glycoside hydrolase 12 protein is a major virulence factor during soybean infection and is recognized as a PAMP (Ma et al ., ), and so are VdEG1 and VdEG3 from V. dahliae (Gui et al , ), suggesting that VdSCP27 and VdSCP126 function in virulence, although they also may be recognized by the host plants to induce immunity. Some fungal effectors are often considered dispensable for virulence due to functional or quantitative redundancy (Sharpee and Dean, ), as many PAMPs have been found in V. dahliae (de Jonge et al , ; Zhou et al , ; Santhanam et al , ; Gui et al , ; ) and deletion of VdSCP113 singly perhaps is unable to alter the pathogen virulence. Another hypothesis is that the effectors initially function in virulence and subsequently are recognized by the host to induce immunity as a result of a long coevolutionary arms race, thereby also forcing a dual role during host–pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, diversity hot spots were identified in the cutinase amino acid sequence when 200 fungal species were compared and this could be explained by divergent evolution allowing different functions of cutinase enzyme in plant pathogenic fungi. Gui et al () conducted functional analysis of 13 cutinase genes (VdCUTs) and found significant sequence divergence in cutinase family members in the genome of Verticillium dahliae Vd991.…”
Section: Discussionmentioning
confidence: 99%
“…In order to successfully invade into host plant, plant pathogenic fungi are expected to produce and secrete multiple extracellular degrading enzymes such as cutinase for the degradation of cuticle [33], cell wall degrading enzymes (pectinase, cellulase and hemicellulase) [34], and cytomembrane and cell inclusion degrading enzymes (protease and lipase) [35,36]. 9 cutinases were identified both in HGCC, CCP and UM591 genomes (Table S1).…”
Section: Protein Families Involved In Degrading Plant Cuticle Cell Wmentioning
confidence: 99%